Comparison of Feasibility, Efficacy and Patient Acceptability of Manual Vacuum Aspiration Vs Sublingual Misoprostol in Early Pregnancy Loss - Arif, Nadia; Zafar, Bushra; Ahmed, Raja Qaseem; Shehzad, Farrukh (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare feasibility, efficacy and patient acceptability of manual vacuum aspiration with sublingual Misoprostol in early pregnancy loss. Study Design: Comparative prospective study. Place and Duration of Study: Gynecology and Obstetrics Department, Combined Military Hospital Okara Pakistan, from Aug 2019 to Apr 2020. Methodology: 200 Patients with early pregnancy loss (missed, incomplete abortion) at gestational age 6 to 12 weeks were randomly allocated to Manual vacuum aspiration (group A) and oral Misoprostol (group B) by lottery methods. Manual vacuum aspiration was done in the outpatient department. While in Group B, oral Misoprostol was given with a protocol 600 micro gram sublingual stat observe for 1 hour for any complication. Afterwards, they were given Misoprostol 600 micrograms sublingual, 3 hourly total of 2 doses. Patients from both groups were called for follow-up after one week. Results: Efficacy, feasibility and patient acceptability was 88%; p-value <0.001, 95%; p-value <0.001 and 97% respectively in manual vacuum aspiration group as compared to 64%, 68% and 70% in sublingual Misoprostol group. There were fewer systemic side effects and fewer visits in manual vacuum aspiration group 1 vs 3 in the sublingual Misoprostol group. Conclusion: Manual vacuum aspiration is more effective than Misoprostol as it has no systemic effects. Both options are cheap and can be achieved in outpatient settings. However, manual vacuum aspiration provides complete evacuation and is a good option for low resource settings and a developing country like Pakistan with frequent electricity disruptions. It offers a substantial saving on resources, cost and...